Use of Ecolabels in Promoting Exports from Developing Countries to Developed Countries: Lessons from the Indian LeatherFootwear Industry - Parashar Kulkarni (Fondazione Eni Enrico Mattei (FEEM), 2005)
This paper tries to understand whether importers in the North are able to push exporters in the South towards sustainable production, with the help of a case study of the Indian leather industry. After providing a short description of the global leather footwear industry, the first section provides insights into the competitive advantages of different countries, characteristics of developing country exporters and the difference between large and small European buyers of Indian leather footwear. The subsequent section provides an insight into the different chains of influence that exist in trying to make international trade more sustainable with the help of a broad understanding of the means, their effectiveness, their constraints and a few examples of such chains of influence. Section four studies whether ecolabels are in a position to be suitable indicators of sustainability. Further it delves into understanding the perspectives of consumers, producers and regulators on whether ecolabels are useful in promoting sustainable exports. The explanation of how ecolabels conflict with brand dynamics is quite interesting. The policy measures provide clear options for targeting sustainable production. Suggestions include use of eco-elasticity indicator, toolbox approach to environment policy, introducing comprehensive sustainability labels, maintaining a level of mandatory legislations as well as a constructive effort to increase transparency in supply chains. The annexure include the research methodology adopted for the paper, the reason for choosing Europe as destination for the research, a brief overview about types of ecolabels and a small description of integrated product policies.
Keywords: F18; 330; Ecolabels; Export promotion; Leather footwear; Market access; Umweltzeichen; Außenhandelsförderung; Schuhindustrie; Indien